2012
DOI: 10.1186/1752-153x-6-133
|View full text |Cite
|
Sign up to set email alerts
|

Alpha chymotrypsin coated clusters of Fe3O4nanoparticles for biocatalysis in low water media

Abstract: BackgroundEnzymes in low water containing non aqueous media are useful for organic synthesis. For example, hydrolases in such media can be used for synthetic purposes. Initial work in this area was carried out with lyophilized powders of enzymes. These were found to have poor activity. Drying (removing bulk water) by precipitation turned out to be a better approach. As enzymes in such media are heterogeneous catalysts, spreading these precipitates over a large surface gave even better results. In this context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, Dik et al reported that an externally applied magnetic field improved the activity of l -asparaginase adsorbed on iron oxide nanoparticles. 112 Extensive work has been carried out on enzyme immobilization on iron oxide nanoparticles; 113–117 it may be interesting to investigate this phenomenon with a wider range of immobilised enzymes.…”
Section: How Biocatalysts Have Emerged As Enablers In White and Grey ...mentioning
confidence: 99%
“…Recently, Dik et al reported that an externally applied magnetic field improved the activity of l -asparaginase adsorbed on iron oxide nanoparticles. 112 Extensive work has been carried out on enzyme immobilization on iron oxide nanoparticles; 113–117 it may be interesting to investigate this phenomenon with a wider range of immobilised enzymes.…”
Section: How Biocatalysts Have Emerged As Enablers In White and Grey ...mentioning
confidence: 99%